Optimization Of Tablet Formulation of Ethanol Extract of Basin (Ocimum basilicum L.) As Antioxidant with Variations of Pregelatinized Starch and Explotab - Sa`adah, Hayatus; Sya’diyah, Halimatus; Ansyory, Achmad Kadri; Supomo, Supomo (Jurnal Ilmiah Medicamento, 2026)
Background: Basil (Ocimum basilicum L.) is recognized as a rich botanical source of secondary metabolites that exhibit notable antioxidant properties.Objective: The present investigation sought to examine how variations in disintegrant type and proportion—specifically pregelatinized starch and Explotab—influenced the physical characteristics and antioxidant capacity of tablets prepared from basil leaf ethanol extract.Methods: Three distinct formulations were developed based on differing pregelatinized starch-to-Explotab ratios: Formula I (0:1), Formula II (1:1), and Formula III (1:0). All prepared tablets underwent comprehensive physical evaluation and stability assessment, while antioxidant potential was quantified through the DPPH radical scavenging method. The formulation optimization process employed the Simplex Lattice Design (SLD) methodology executed via Design-Expert® version 13 software.Results: Experimental findings demonstrated that the ratio variation between pregelatinized starch and Explotab exerted measurable effects on both granule and tablet physical attributes. Specifically, pregelatinized starch was found to predominantly elevate bulk density, weight uniformity, and disintegration time, whereas Explotab exhibited a stronger regulatory influence over moisture content, flow rate, Carr’s index, and tablet friability. The optimal formulation was identified as containing 6.72% pregelatinized starch combined with 1.27% Explotab. Notably, all three formulations demonstrated very strong antioxidant activity, with IC₅₀ values spanning from 33.78 to 39.52 ppm. One-way ANOVA statistical evaluation revealed no significant interformulation differences (p > 0.05).Conclusion: The collective data supports the conclusion that a strategic combination of pregelatinized starch and Explotab yields basil extract tablets with satisfactory physical quality alongside preserved antioxidant efficacy.